The role of financing accessibility on boosting micro scale coastal communities’ fisheries related business activities: case study from Kei Islands - Frischilla Pentury (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Financial capital is one of the integral factors in moving the business. Accessing the financial sources either from loan and/or monetize the asset is key to boost the ability to gain and gather the capital needed to expand and maintain the business flow. Fisheries and marine related business activities included, even so to small medium enterprises and more so to micro scale of fisheries business. In small islands region of Kei Islands, most of coastal communities that currently running fisheries and marine related business activities namely fishing, marine farming, and marine ecotourism are in micro scale based. Many researchers and studies agreed that for micro scale, it is hard to access the fund due to lack of collateral own by them. Therefore, the aimed of this the role of financing accessibility to support to production of fisheries and marine of coastal communities in Kei Islands. In order to do so, the methodology of study was k-mean clustering to obtain micro scale actors that willing to and able to access the financing aid either from state bank, lending institution and private entities. This study also used multi-linear regression analysis to view the role of the financing accessibility to coastal communities’ fisheries and marine production. The respondent of the study were coastal communities who are sellers, fishermen, marine farmer and micro scale actors in the region with 103 respondents. Data collecting using purposive sampling, the data collecting start from May to August 2021. The result of the study we have found that, more communities were able to access and have higher need for the financial entities than those who unable and have lower interest for financing accessibility. Moreover, the number of expenses, the type of fisheries and marine activities and sex were three factors that influence the production of fisheries and marine activities.